CYTOLOGICAL FEATURES OF FENSPIRIDE USAGE IN TREATMENT OF CHRONIC EXUDATIVE OTITIS MEDIA - O. Yu. Mezentseva; F. N. Zavjyalov; A. A. Vorobjeva; L. P. Popova; M. V. Rodionova ("Paediatrician" Publishers LLC, 2012)
The cytological investigation of exudates, obtained during tympanostomies, showed the predomination of inflammatory-regenerative cytograms types when using Fenspiride (Eurespal) in treatment of secretory stage of chronic exudative otitis media. Received data confirm, that treatment with this drug shortens the course of exudative otitis media and contributes to more rapid change from destructive to reparative stage of inflammation, which prevents the development of adhesive process in the middle ear.